2019
DOI: 10.1038/s41388-019-0950-z
|View full text |Cite|
|
Sign up to set email alerts
|

PKCα is required for Akt-mTORC1 activation in non-small cell lung carcinoma (NSCLC) with EGFR mutation

Abstract: Constitutively active epidermal growth factor receptor (EGFR) mutations play critical roles in the development and progression of non‐small cell lung cancer (NSCLC). Patients with EGFR mutations are initially sensitive to EGFR‐tyrosine kinase inhibitors; however, they eventually develop drug resistance. Therefore, thorough understanding of mutant EGFR signaling is crucial in order to avoid such resistance and develop novel control therapeutic strategies. In the present study, we observed high PKCα expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
(62 reference statements)
1
11
0
Order By: Relevance
“…The role of PRKCA as a tumorigenic marker is plausible: Protein kinase C isoforms have been long identified as the intracellular receptors of phorbol esters that promote tumor formation during two-stage chemical-induced carcinogenesis in mouse skin [ 36 , 37 ]. Subsequently, PRKCA has been shown to intersect with the MAPK/ERK and PI3K/AKT pathways, which are frequently active in several cancer types, promoting tumor progression by suppressing apoptosis and inducing proliferation, migration, invasion and angiogenesis [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The role of PRKCA as a tumorigenic marker is plausible: Protein kinase C isoforms have been long identified as the intracellular receptors of phorbol esters that promote tumor formation during two-stage chemical-induced carcinogenesis in mouse skin [ 36 , 37 ]. Subsequently, PRKCA has been shown to intersect with the MAPK/ERK and PI3K/AKT pathways, which are frequently active in several cancer types, promoting tumor progression by suppressing apoptosis and inducing proliferation, migration, invasion and angiogenesis [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…patients in recent decades could suggest a role of environmental, dietary or lifestyle factors, though alcohol, smoking and HPV do not play a substantial role. [40][41][42][43][44]. Both pathways are known to promote cell growth, proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically, PKCδ upregulation correlated negatively with OS in TKI-treated Δ EGFR NSCLC patients [ 84 ]. Interestingly, our recently published work has demonstrated that there is a Δ EGFR -independent selection for high PKCα protein expression in NSCLC, and a Δ EGFR -dependent activation of PKCα that translates to constitutive downstream signaling to AKT/mTOR pathway [ 113 ]. In BRAF / KRAS mutant NSCLC, PKCα was shown to modulate sensitivity to chemotherapy via mediating MDR1 expression and RLIP76 phosphorylation ( Figure 4 ) [ 40 , 41 , 42 ].…”
Section: Pkc-mediated Resistance Acquisition and Drug Sensitivity In Nsclcmentioning
confidence: 99%